Implementation Of Time Out Procedure To Reduce Operation Side Identification Errors At St Elisabeth Hospital Bekasi - Fauzi, Achmad; Kusumawardani, Maharani Dyah (Jurnal Ners, 2025)
Background: In response to this, WHO has launched a global movement to promote safe surgery, which gave birth to the surgical safety checklist. The use of this checklist has been shown to reduce mortality by 50% and reduce complications from 11% to 7%. Objective: The effect of the Implementation of Time Out Procedure on Reducing Errors in Identification of the Surgical Site at St. Elisabeth Hospital, Bekasi Research Method: cross-sectional research method, with data analysis carried out univariately and bivariately with the chi square test. Research Results: Description of the results of the characteristics of respondents based on age, the most are in patients who underwent with the age of 46-55 years, the most gender is in patients who underwent surgery, the female gender is 36 respondents (56.2%), the most type of surgery in patients with major surgery is 41 respondents (64%). Based on the results of the chi square statistical test in this study, the results of the p-value were 0.000 <0.05 H0 was rejected and Ha was accepted, meaning that there was a significant relationship between the Time Out Procedure operation and the occurrence of errors in identifying the side of the operation in the surgical room of St. Elisabeth Hospital, Bekasi in 2025. Conclusion: There is an influence between Time Out Procedure surgery and the incident of error opening the surgical side in the ST Elisabeth Bekasi Hospital surgical room with a p-value of 0.000